2008
DOI: 10.1177/0269215508093331
|View full text |Cite
|
Sign up to set email alerts
|

How much do the benefits cost? Effects of a home-based training programme on cardiovascular fitness, quality of life, programme cost and adherence for patients with coronary disease

Abstract: The programme seems to provide an efficient low-cost approach to cardiac rehabilitation in low-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 23 publications
4
56
0
Order By: Relevance
“…For example, motivational letters in particular are a very low-cost intervention, which warrant testing in such contexts. The structured health professional-led contacts via phone calls or home visits has been practiced in MICs, particularly with the home-based CR model in Iran as well as in Brazil, where such models of CR are reported to have low cost [29,68].…”
Section: Discussionmentioning
confidence: 99%
“…For example, motivational letters in particular are a very low-cost intervention, which warrant testing in such contexts. The structured health professional-led contacts via phone calls or home visits has been practiced in MICs, particularly with the home-based CR model in Iran as well as in Brazil, where such models of CR are reported to have low cost [29,68].…”
Section: Discussionmentioning
confidence: 99%
“…The cost of administering CR is poorly studied, with only a few small studies in the area. 28 A simplified cost analysis with some attendant assumptions was included as part of a recent Canadian CR study. The cost-utility ratio those investigators found for CR ($6000 per life-year gained) was within an economically attractive threshol" for costeffectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it appears the telerehabilitation group improved significantly from baseline in quality of life for patients with cardiac (Chien et al, 2011;Oka et al, 2000;Salvetti et al, 2008;Servantes et al, 2011) and respiratory conditions (Maltais et al, 2008;Oh, 2003). For example, when considering the amount of improvement in quality of life compared with baseline, the difference (95% CI) between telerehabilitation and no intervention was seven (1 to 12) points on the 105-point Minnesota living with heart failure questionnaire (Chien et al, 2011).…”
Section: Quality Of Lifementioning
confidence: 96%
“…Two studies found no significant difference in post-program VO2peak between telerehabilitation and no intervention in patients with cardiac conditions (see Figure 2-3) (Brubaker et al, 2000;Oka et al, 2000). Conversely, some studies found a significant improvement in VO2peak following telerehabilitation for patients with cardiac conditions, whereas no intervention group showed a decline (Salvetti et al, 2008;Servantes et al, 2011). Factors contributing to this discrepancy remain unclear.…”
Section: Vo2peakmentioning
confidence: 99%
See 1 more Smart Citation